2019
DOI: 10.1111/agec.12518
|View full text |Cite
|
Sign up to set email alerts
|

Peer effects in the diffusion of water‐saving agricultural technologies

Abstract: We investigate the role of peer effects in the diffusion of an important water-saving irrigation technology: low energy precise application (LEPA). Using detailed irrigation behavior data for growers in the High Plains Aquifer region of Kansas covering 1990-2014, we find clear evidence of peer influence in adoption of LEPA, net of environmental factors. Specifically, an additional neighboring LEPA installation within 1 km increases the probability of adoption by about 0.3 percentage points, on average, and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Endogenous effects reflect technological spillovers in the diffusion of irrigation, for example, through the transmission of successful experiences (or imitation) of irrigation in neighbouring municipalities (Richards 2018). Similar results for irrigation technologies have been reported by Genius et al (2014) and Sampson and Perry (2019).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Endogenous effects reflect technological spillovers in the diffusion of irrigation, for example, through the transmission of successful experiences (or imitation) of irrigation in neighbouring municipalities (Richards 2018). Similar results for irrigation technologies have been reported by Genius et al (2014) and Sampson and Perry (2019).…”
Section: Discussionsupporting
confidence: 67%
“…We analysed spatial spillover effects on the diffusion of more efficient irrigation strategies in SP. Spatial spillovers are linked to peer effects and can be understood in the context of agriculture as farmers' influence in a particular farmer's decision-making (Sampson and Perry 2019). The estimation of spillover effects is a topic of growing concern in economic literature, and few studies have specifically analysed irrigation in agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout this systematic review of the peer-reviewed global literature, it was clear that a paucity of social research was comprehended as a knowledge gap in understanding why PCA, DA, and RA have failed to gain widespread adoption. The following list of studies explore and indeed insist upon more in-depth social science research in the areas of precision conservation agriculture [13,32,35,38,[44][45][46]49,[66][67][68][69]82,[84][85][86][87][88], digital agriculture [22,47,[54][55][56]70], and resilient agriculture [42,43,48,[57][58][59][60][61][62][63]89].…”
Section: Barriers To Adoptionmentioning
confidence: 99%
“…Since DTWVs are usually knowledge-intensive, the imitation helps reduce the costs (e.g., information searching costs) of converting from traditional varieties to DTWVs. For example, Sampson and Perry (2019) found that a neighboring adopter significantly increases the probability of farmers' adoption of low-energy precise application in the United States. The second sub-pathway underscores the role of the information spillover.…”
Section: Theoretical Frameworkmentioning
confidence: 99%